Efeito de cultivares de repolho e doses de extrato aquoso de nim na alimentação e biologia de Plutella xylostella (linnaeus) (lepidoptera: Plutellidae) - Boiça Júnior, Arlindo Leal [UNESP]; Janini, Júlio Cesar [UNESP]; de Souza, Bruno Henrique Sardinha [UNESP]; Rodrigues, Nara Elisa Lobato [UNESP] (My University, 2013)
The isolated and associated effects of cabbage cultivars Ruby Ball and Chato de Quintal and aqueous extract of seeds of fruits of neem (Azadirachta indica A. Juss.) were evaluated in the concentrations of 5 and 10% on Plutella xylostella (L.) attractiveness, feeding and development. In free-choice no-preference for feeding test, leaf discs of each treatment were placed in Petri dishes where three caterpillars/treatment were released while in no-choice test two caterpillars were placed in Petri dishes with one leaf disc in each dish. In the biology test, neonate larvae were transferred to Petri dishes in the proportion of one per dish, whereas the biological parameters were evaluated: larvae mortality after 1, 3 and 5 days; pupae mortality; total mortality; six day-old larvae weight; 24 hour-old pupae; and adult longevity. Cultivar Ruby Ball showed lower attractiveness to the caterpillars in free-choice test. Neem extract in both concentrations was repellent to the caterpillars in free-choice test. There were no differences in the dry mass consumed by the caterpillars in free-choice and no-choice tests. There were no differences in larval, pupal and total mortality between the cultivars. Both doses of neem extract were equally efficient in the mortality of the diamondback moth. There were no differences in caterpillars and pupae weight and in the longevity of the adults of P. xyostella between the cultivars.

Avaliaram-se os efeitos isolados e associados das cultivares de repolho Ruby Ball e Chato de Quintal e o extrato aquoso de amêndoas de frutos de nim (Azadirachta indica A. Juss.) nas concentrações de 5 e 10% sobre a atratividade, alimentação e desenvolvimento de Plutella xylostella (L.). No teste de não preferência para alimentação com chance de escolha, discos foliares de cada tratamento foram dispostos em placas de Petri onde foram liberadas três lagartas/tratamento, enquanto no teste sem chance de escolha duas lagartas foram colocadas em placas de Petri contendo um disco foliar em cada placa. No teste de biologia, lagartas recém-eclodidas foram transferidas para placas de Petri, na proporção de uma por placa, onde foram avaliados os parâmetros biológicos: mortalidade larval após 1, 3 e 5 dias; mortalidade pupal; mortalidade total; peso de lagartas com seis dias de idade; peso de pupas com 24 horas de idade; e longevidade de adultos. A cultivar Ruby Ball apresentou menor atratividade às lagartas no teste com chance de escolha. O extrato de nim em ambas as concentrações foi considerado repelente no teste com chance de escolha. Não houve diferença na massa foliar seca consumida pelas larvas, nos testes com e sem chance de escolha. Também não foi observada diferença na mortalidade larval, pupal e total entre as cultivares. Ambas as doses do extrato de nim foram igualmente eficientes na mortalidade da traça-das-crucíferas. Não houve diferença do peso de lagartas e pupas e da longevidade dos adultos de P. xylostella entre as cultivares.
Effect of cabbage cultivars and doses of aqueous extrat of neem on feeding and biology of Plutella xylostella (linnaeus) (lepidoptera: Plutellidae)
Keywords: Azadirachta indica; Diamondback moth; Host plant resistance; Insecticide plants